Assessment of Nurse’s knowledge about the Infection Control in the Hemodialysis (HD) Unit (Journal of Pharmaceutical Negative Results, 2023)
Background:  The vascular access is importance for the patient with renal failure to doing the hemodialysis and high risk for infection and this increase the risk of life-threatening from the vascular access of dialysis1 the Centers for Disease Control and Prevention (CDC) labeled many measures to prevent and break of the infection process through hand hygiene, wear gloves, gown and environmental cleaning2Methods:  Hospital based – cross sectional study. Participants were randomly assigned to the intervention. Level of knowledge were measured at baseline and at 1 month, involved a systematic collection, analysis and interpretation of data to evaluate the current knowledge. The sample consist of 50 persons and that who were available during study period.Result: The results showed 40 % of population have poo knowledge about the wearing gloves and 70% have good knowledge about the fistula care but the 34% of participants have sufficient knowledge about the universal precautions should be used in HD, 26% don’t know about spread of infection in dialysis.Conclusion: Based on the results of current study, we concluded help enhance nursing staff need more education training more knowledge about importance infection control in HD unit to help and minimize the rate of infection in the HD field and we must educate the nursing staff about stander precaution, sterilization, care of fistula, dialysis equipment and machine sterilization, environmental issues and educate about importance of safety removal of waste of HD.